MAINTENANCE OF POMEGRANATE FRUIT QUALITY BY COATING WITH FLAXSEED, BLACK SEED OILS, AND CHITOSAN DURING DIFFERENT STORAGE PERIODS - Heshw wafa Rashid Ali,; Ali Muhi Aldeen Omar Aljabary, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was conducted on the Salakhani pomegranate fruit, to study the impact of coating with (0.5 and 1) % flaxseed, (0.5 and 1)% black seed oil, and (0.5 and 1)% chitosan plus control treatment and with five storage periods. The fruits were harvested at full ripening stage on 2/11/2020 from a private orchard. The fruits were divided into groups according to the concentrations of flaxseed oil, black seed oil, and chitosan, as well as the control treatment and storage periods. Fruits were dried well after the coating process and placed in special boxes (carton boxes), the fruits were stored for five storage periods at a temperature of 5±1°C and with 85-90% relative humidity. The factorial experiment within the complete randomized design was used with three replicates. Coating fruits with flaxseed oil at 0.5% and 1% while black seed oil and chitosan at 1% had an effect in reducing the weight loss of fruits during storage. All coated treatments caused to significantly maintain the visual evaluation quality, and decrease the chilling injury of fruits, also increased the total soluble solid, total sugars and anthocyanin in juice content than the control except for coating 0.5% flaxseed oil. The storage for 4 months was significantly superior to the percentage of total sugars, the content of anthocyanin, maintained the visual evaluation quality and decreased the chilling injury of fruits.